FREQUENCY OF ACUTE ISCHEMIC MITRAL REGURGITATION IN PATIENTS OF ACUTE ST-SEGMENT ELEVATED MYOCARDIAL INFARCTION IN PATIENTS PRESENTING AT TERTIARY CARE HOSPITAL OF PESHAWAR - ULLAH , K; ALI , J; SAJJAD , W; RAHIM , A; NAWAZ , S; ULLAH , R (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to determine the frequency of acute ischemic mitral regurgitation in patients with acute ST-segment elevated myocardial infarction. This descriptive cross-sectional study was conducted at the Cardiology Department of Lady Reading Hospital in Peshawar from March 18, 2019, to September 18, 2019. The study was conducted at Peshawar’s Cardiology Department of Lady Reading Hospital. A total of 126 patients were observed, and all of them were subjected to a detailed history, including their past medical history, age, sex, and smoking status. They also underwent a routine physical examination baseline investigation, including ECG (cardiofax) and transthoracic echocardiography (Siemens’ Accuson CV-70). The data was recorded in a pre-designed proforma. The mean age of the patients in this study was 53 years, with a standard deviation of ±11.23. 68% of the patients were male, while 32% were female. Additionally, 5% of the patients had ischemic mitral regurgitation, while 95% of the patients did not have ischemic mitral regurgitation. This study concludes that the frequency of acute ischemic mitral regurgitation in patients with acute ST-segment elevated myocardial infarction was 5%.